The Mise-en-scene aspects in the scene of Soedirman journey to the Sobo village in Pacitan Created By Viva Westi - Shafna Lailatul Fida (Program Studi Film dan Televisi Universitas Jember, 2021)
This study discusses aspects of the mise-en-scene in the journey of General Soedirman to the village of Sobo Pacitan which focuses on four elements of the mise-en-scene including settings, costumes and make-up, lighting, most recently the player's movements. The mise-en-scene aspects contained in the film General Sudirman were analyzed using the Aesthetic theory A.A.M Djelantik. The type of writing used is qualitative research. Data collection techniques are carried out using observation, documentation and literature study techniques. Data analysis techniques used are data reduction, data presentation, and drawing conclusions and verification. Based on the results of the study, there were 8 scenes of General Soedirman's journey to Sobo Pacitan Village. Discussion of the settings, properties, costumes and make-up of each scene has differences in each scene. The aspect of mise-en-scene is able to produce a sense of space and time, mood setting, and describe the character of the film with the support of settings, properties, costumes and make-up made as similar as possible to events in 1948. Discussion of the aesthetics contained in the film has 3 aspects namely (1). The form or appearance contained in each scene has a unity, emphasis and balance that reinforces the identity of each scene. (2). Weight or content (content, substance) describes the atmosphere in each scene. (3). The appearance, presentation of each scene differs in each setting, costume and make-up, lighting, and player movement.